Gain of C-Ala enables AlaRS to target the L-shaped tRNAAla. Issue 4 (31st January 2022) - Antika, Titi Rindi; Chrestella, Dea Jolie; Ivanesthi, Indira Rizqita; Rida, Gita Riswana Nawung; Chen, Kuan-Yu; Liu, Fu-Guo; Lee, Yi-Chung; Chen, Yu-Wei; Tseng, Yi-Kuan; Wang, Chien-Chia
Abstract: Unlike many other aminoacyl-tRNA synthetases, alanyl-tRNA synthetase (AlaRS) retains a conserved prototype structure throughout biology. While Caenorhabditis elegans cytoplasmic AlaRS (CeAlaRSc ) retains the prototype structure, its mitochondrial counterpart (CeAlaRSm ) contains only a residual C-terminal domain (C-Ala). We demonstrated herein that the C-Ala domain from CeAlaRSc robustly binds both tRNA and DNA. It bound different tRNAs but preferred tRNA Ala . Deletion of this domain from CeAlaRSc sharply reduced its aminoacylation activity, while fusion of this domain to CeAlaRSm selectively and distinctly enhanced its aminoacylation activity toward the elbow-containing (or L-shaped) tRNA Ala . Phylogenetic analysis showed that CeAlaRSm once possessed the C-Ala domain but later lost most of it during evolution, perhaps in response to the deletion of the T-arm (part of the elbow) from its cognate tRNA. This study underscores the evolutionary gain of C-Ala for docking AlaRS to the L-shaped tRNA Ala .